1997
DOI: 10.1029/97ja00903
|View full text |Cite
|
Sign up to set email alerts
|

Statistical nature of geomagnetic storms

Abstract: Abstract. On the basis of geomagnetic activity indices and solar wind parameters, a superposed epoch analysis has been conducted for more than 300 geomagnetic storms. The intensity of magnetic storms is found to depend on the duration of the main phase; larger storms have longer timescales. For intense storms, however, not only the duration of energy injection into the ring current but also the strength of injection is important in determining their size. It is confirmed that the southward component of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(157 citation statements)
references
References 33 publications
14
137
6
Order By: Relevance
“…Their average duration is shorter than typically observed [Yokoyama and Kamide, 1997], primarily because numerical difficulties prevented us from modeling longer time periods with the RCM-E. With the test particle tracing code, we can calculate the contributions of different sources as a function of storm intensity. Figure 8a shows that the total plasma energy inside geosynchronous orbit and that contributed by bubbles are well correlated with Dst index.…”
Section: Results From 20 Idealized Stormsmentioning
confidence: 99%
“…Their average duration is shorter than typically observed [Yokoyama and Kamide, 1997], primarily because numerical difficulties prevented us from modeling longer time periods with the RCM-E. With the test particle tracing code, we can calculate the contributions of different sources as a function of storm intensity. Figure 8a shows that the total plasma energy inside geosynchronous orbit and that contributed by bubbles are well correlated with Dst index.…”
Section: Results From 20 Idealized Stormsmentioning
confidence: 99%
“…Observational studies [e.g., Tsurutani et al, 1988; Yokoyama and Kamide, 1997; Kamide et al, 1998] show that especially intense magnetic storms (e.g., those during which Dst attains values < -toe nT) are often associated with two distinct intervals of large southward IMF Bz and with two distinct intervals of increasingly negative Dst indicating that a second ring-current enhance-fomia [e.g., Kamide et al, 1997], suggested that perhaps the ring current enhancement attained during the first stage of a double-dip storm provides a necessary seed population for the more intense ring current to be attained during the second enhancement. If so, then it seems that a double-dip storm would inherently attain a stronger ring current than a comparable single-dip storm.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 13 shows the results of a superposed epoch analyses by Yokoyama and Kamide (1997) and Kamide et al (1998b), for an examination of single storms and double storms. The top panel gives the AL index for single and double storm events.…”
Section: Multiple Magnetic Stormsmentioning
confidence: 99%
“…In that "classic" statistical study, they identified magnetic storms on the basis of the existence of SSCs, thus excluding the so-called gradual storms. In more recent studies, Taylor et al (1994), Loewe and Prölss (1997), and Yokoyama and Kamide (1997) have conducted statistical studies of geomagnetic storms in which Dst variations were compared with auroral electrojet activity, as well as with their interplanetary causes. These studies followed essentially the same approach as Sugiura and Chapman, where the variability in duration for different storms was obscured in their averaging process.…”
Section: Two-step Growth In the Ring Currentmentioning
confidence: 99%
See 1 more Smart Citation